The Role of Ekphrasis in Creating Hierotopy in “Mirozhsky Poems” by Vsevolod Rozhnyatovsky - Ilona V. Moteyunayte (Литературный факт, 2023)
The article is devoted to the analysis of Vsevolod Rozhnyatovsky’s “Mirozhsky poems” (2013), which demonstrates the sacralization of the place described therein. The author shows how the title toponym exists in the cultural consciousness of the Pskovites (the name of the river is absorbed by the name of the temple, which has been turned into a museum). Its composition outlines a peculiar lyrical plot: the subtitles of the book indicate the author’s path from museum work through contact with the Christian religion and art to his own poetic creativity in line with the Christian idea of the Logos. The motif of leaving the temple allows the poet to spread the received in it “knowledge” about the creatureliness of the world to the entire city, which is perceived as a city-temple; the acquired poetic gift turns his book of poems into a kind of prayer for a person of the 20th century, shocked by the meeting with the Christian artistic tradition. The article pays particular attention to the specifics of the poetic ekphrasis, which represents the descriptions of the frescoes of the Transfiguration Cathedral of the Pskov Mirozhsky Monastery. There is the analysis of the position of the subject of the speech (inside the temple but at the same time inside the frescoes plot) based on the contributions of three poems containing the ekphrastic descriptions. This is seen as a kind of illustration to the Pavel Florensky’s ideas of about the icon and church art. The article also indicates to the connections of the 20th century author’s perception of frescoes with the 12th century icon-painting program, which reflects the theological controversy about the union of divine and human God the Son’s nature. The poet’s fascination with this topic attested to the relevance of hierotopy even for the end of the 20th century.